EspañolThe squid of the golden tentacles. An analysis of Chinese fishing in Peru (2000-2020) - Ortega, Federico (2020)
The Chinese capital fishing fleets extract resources on a global scale in the oceans of the world in order to supply their growing domestic market for marine products, such as the giant squid Dosydicus gigas. Like the Asian giant, other powers in the field carry out extractive exploitation in international waters adjacent to the jurisdictions of riparian countries such as Peru and in all the seas of the world, fed by generous subsidies. This does not prevent fleets from sometimes engaging in practices such as illegal, unreported, unregulated fishing and the exploitation of workers, within the latent danger of overexploitation of maritime resources, with the damage to biodiversity and the ecosystem that this entails. The process is complemented by insertion into the legal fishing circuit, in this case, in Peru, through mergers and acquisitions of various companies in the field. In the context of these extractivist practices, and in the framework of a hybrid and fragmented world war, a conflict develops between China and the United States for control of the South Pacific, in which the North American government leads actions and criticisms against the Chinese policies, using the speech of various Non-Governmental Organizations. The actions and positions of both sides have geostrategic implications, which peaked with the appearance of the Chinese fleets in the South Pacific during the months of August to October 2020.